The effect of short-term socio-economic and demographic change on landuse dynamics and its corresponding geomorphic response with relation to water erosion in a tropical mountainous catchment, Ecuador - VANACKER, Veerle; GOVERS, Gerard; BARROS, Sandra; POESEN, Jean; DECKERS, Jozef (Landscape ecology, 2003)
The analysis of aerial photographs over a 33-year period (1962–1995) shows that land use in the study catchment is highly dynamic as a response to the land reform programs of the 1960s and 1970s and a strong population increase. The secondary forest is increasingly replaced by grassland while old grasslands are now used as cultivated land. Despite the increased pressure on the land, the upward movement of agricultural activity and the concurrent deforestation, the overall forest cover did not decline. The deforestation in the uplands is compensated for by a regeneration of secondary forest on abandoned rangelands and afforestation with Eucalyptus trees in the low-lying areas. The land use changes resulted in a strong decrease of the areas subject to intense soil degradation: afforestation with Eucalyptus trees on degraded lands was successful in controlling soil erosion in the lower parts of the catchment. The relationship between land use and sediment load in the river system is not straightforward. Statistical analysis of a time series of suspended sediment concentrations, which were measured at the outlet of three distinctive sub-catchments for a six-year period (1994 – 2000), revealed that the geomorphic response of the river system is not only dependent on the land use and the area affected by water erosion, but also on the spatial connectivity between sediment producing areas and the river network.